TRANSFORMASI PENDIDIKAN INDONESIA DI ERA DIGITAL: ANTARA HARAPAN DAN TANTANGAN - Abdurrohman; Tasya Salsabilla; Moh. Ali (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2025)
Educational transformation in the digital era is both inevitable and paradoxical in the Indonesian education system. This qualitative literature review examines the dynamics of this transformation, revealing that digitalization offers the potential for leaps in progress through online learning, digital curricula, and technology platforms that promise equitable access and improved quality. However, a case study in the Cirebon region demonstrates that the reality on the ground is fraught with complex challenges. The multidimensional digital divide—including disparities in internet access infrastructure, low teacher digital pedagogical competency (TPACK), and minimal student digital literacy is a major obstacle, particularly in rural schools. The sharp disparity between schools in urban centers and rural areas has the potential to deepen existing educational inequities. This article concludes that successful transformation should not focus solely on the provision of technology but must be accompanied by an equity centered and pedagogical approach. Therefore, inclusive and sustainable adaptation strategies are needed, such as contextual teacher capacity building, locally based digital content development, equitable infrastructure distribution through multi-stakeholder collaboration, and the implementation of structured hybrid learning models. Only with affirmative and holistic policy synergy can digital education transformation create a national education system that is adaptive, equitable, and truly liberating.